Outpatient opioid prescribing by Alzheimer’s diagnosis among older adults with pain in United States - Yinan Huang; Rajender R Aparasu; Tyler J Varisco (BMC Geriatrics, 2023)
Abstract Objective To examine opioid prescribing practices for pain in older adults with and without Alzheimer’s Disease and Related Dementias (ADRD). Methods This cross-sectional study used National Ambulatory Medical Care Survey data (2014–2016, and 2018). Adults aged ≥ 50 years with pain were analyzed. Prescribing of opioid and concomitant sedative prescriptions (including benzodiazepines, Z-drugs, and barbiturates) were identified by the Multum lexicon code. Multivariable logistic regression evaluated the risk of opioid prescribing or co-prescribing of opioid and sedative associated with ADRD in older adults with pain. Results There were 13,299 office visits in older adults with pain, representing 451.75 million visits. Opioid prescribing occurred in 27.19%; 30% involved co-prescribing of opioids and sedatives. ADRD was not associated with opioid prescribing or co-prescribing of opioid and sedative therapy. Conclusions Opioid and sedatives are commonly prescribed in older adults with pain. Longitudinal studies need to understand the etiology and chronicity of opioid use in older patients, specifically with ADRD.